Investigating the effect of engine noise on power management strategy of a hybrid electric vehicle. (September 2018) - Delkhosh, Mojtaba; Aliramezani, Masoud; Khadem Nahvi, Mahdi
Hybrid electric vehicles (HEVs) have been developed as a promising way to decrease the fuel consumption and emissions of conventional vehicles. Although the noise emission of HEVs is generally lower than that of conventional vehicles, it is still an issue, especially in urban transportation. In this paper, a power management strategy is developed to minimize the annoying noise of the engine for an HEV. This is a modified version of the strategy that was originally established based on the speed ratio of continuously variable transmission (CVT) as the control parameter (CVT-based strategy). The engine combustion noise is assessed using the experimental data of the in-cylinder pressure. Also, the engine brake specific fuel consumption (bsfc) is defined from the experiments. The bsfc and noise data are implemented in the power management strategy. The proposed strategy offers a better performance in terms of reducing engine noise and fuel consumption in comparison with an electric assist control strategy (EACS). On the other hand, the proposed strategy results in a lower level of engine noise than the original CVT-based strategy at the expense of slightly increasing the fuel consumption. For instance, the noise level (dB) in an urban dynamometer driving cycle using the proposed strategy is 49% lower than the case of CVT-based strategy, while the vehicle FC is about 1.1% more than the CVT-based case.